Durability of orbital riveted steel/aluminium joints in salt spray environment. (October 2018) - Di Bella, G.; Borsellino, C.; Calabrese, L.; Proverbio, E.
Highlights: Aluminium alloy/steel joints were realised with an orbital riveting process. Two series of joints were made as a function of the head rivet position. Joints were exposed in salt spray environment up to 10 weeks. Single lap shear tests were performed in order to investigate the effect of corrosion phenomena. Exposure in salt environment significantly affects the resistance of joints. Abstract: In this work, aluminium alloy/steel joints were realised with an orbital riveting process. Two series of joints were made; i.e. in the first, the head of rivet touches with the aluminium sheet; in the second, it touches with the steel one. After their manufacturing, during tests were carried out by exposing the joints to a salt spray fog up to 10 weeks into a climatic chamber. Finally, mechanical tests were performed with the aim to know the effect of corrosion on performance and failure.